Gender Transformative Practices in Early Grade Reading Classrooms (Shiksha Shastra Saurabh, 2018)
This article is based on a research work of 2017 conducted for Plan International Nepal. The research was originally done to assess the reading comprehension of Nepali subject together with basic skills of Mathematics of early graders in grades Two and Three. It focused on assessing existing situation of the early grades’ learning status together with early learning environments in relation to early grade reading. It included field work in 17 schools of Four districts, namely, Morang, Makwanpur, Sindhuli and Banke. It aimed to assess the gender transformative practices in selected classrooms of early grades.